Analisis Senyawa Potensial pada Ginseng Jawa (Talinum paniculatum Gaertn.) dan Daun Kelor (Moringa oleifera) sebagai Anti-Inflamasi dengan Metode Penambatan Molekul (Molecular Docking) - Syifa Farhatunnisa El-Baehaqi; Agniya Dwiputri Aminah; Firdayani Firdayani (Acta Pharmaceutica Indonesia, 2022)
Inflammation is the immune system's response to noxious stimuli such as pathogens, damaged cells, toxic compounds, or radiation. It often causes pain or discomfort. In this study, the search for potential compounds as COX-2 inhibitors from javanese ginseng (Talinum paniculatum Gaertn.) and moringa (Moringa oleifera) was carried out. The method used in this research was molecular docking by the Molegro Virtual Docker. Some assessments that have been done in this research are Rerank Score, Hbond interaction, and Lipinski Rule of Five. The result showed that COX-2 inhibitor compounds potential are chlorogenic acid and quercetin with the Rerank Score - 112.802 and -95.8476, respectively. The results show that chlorogenic acid and quercetin have Rerank scores of -112.802 and -95.8476, respectively. Thus, the two compounds can be predicted to have the potential as COX-2 inhibitors.